Bacteria in agrobiology : crop productivity - Aeron, Abhinav; Maheshwari, D. K.; Saraf, Meenu (New York : Springer, 2013)
This book examines the role of beneficial bacteria in crop growth, increased nutrient uptake and mobilization, and defense against phytopathogens. It details a diverse group of agricultural crops and medicinal plants as well as PGPR-mediated bioremediation
Includes bibliographical references and index
Keywords: Bacteriology, Agricultural